When Financial Aid Is Not Enough: The Smart Indonesia Program, Social Capital, and Learning Quality at MAN 1 Pidie - Fitriadi Fitriadi; Saifuddin Saifuddin; Fauzi Fauzi; Mursyidin Mursyidin; Alwi Alwi (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
The Smart Indonesia Program (Program Indonesia Pintar, PIP) is designed to reduce educational costs for students from poor and vulnerable households. Its role in widening access is widely recognised, yet its contribution to learning quality remains less direct. This article examines how PIP shaped educational access and learning quality at Madrasah Aliyah Negeri 1 Pidie, Aceh, Indonesia, with particular attention to the role of social capital. Using a qualitative case study design, data were collected through observation, semi-structured interviews with beneficiary students, parents, teachers, and the madrasah principal, and documentation related to programme implementation. The analysis draws on Bourdieu’s concept of social capital to explain why financial assistance does not always produce equal educational outcomes. PIP reduced routine schooling costs, including uniforms, books, stationery, and transportation, and helped students from low-income families remain enrolled. It also increased confidence and supported school participation among several beneficiaries. However, its influence on learning quality was less consistent. Some students continued to show weak motivation, low discipline, and limited academic improvement, while the funds were often used for basic schooling needs rather than academic enrichment such as tutoring, additional learning materials, skills training, or digital learning resources. The programme’s educational value depended on parental guidance, teacher mentoring, communication between school and family, school monitoring, and the efficiency of fund disbursement. The article argues that PIP provides economic capital, but its conversion into stronger learning quality requires social capital, cultural resources, and institutional support. Financial aid can keep students in school, but learning quality depends on a broader support system that connects economic assistance with social guidance and academic development.